Method to Investigate Railway Vehicles Forced Oscillations in Curves in the Inertial Reference System - V. M. Kondrashov (Вестник Научно-исследовательского института железнодорожного транспорта)
Classical procedure prescribes to examine mechanical systems motion in non-inertial reference frames moving in relation to stationary inertial frame. In the present paper there is proposed method to examine forced oscillations of railway vehicles caused by curved track irregularities in plane and profile in inertial reference system, allowing for much-simplified setting up a problem and reduced computation time while making assessment of vehicle dynamics, its components loading and wear indices of a wheel/rail friction pair without loss of accuracy. Object of examination is represented with four-axle vehicle described by a set of non-linear differential equations. There are given computation results as exemplified by such vehicle movement in curves with different radii.